2018
DOI: 10.5588/ijtld.17.0483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pyrazinamide resistance on multidrug-resistant tuberculosis in Karakalpakstan, Uzbekistan

Abstract: Treatment of MDR-TB with a standard PZA regimen does not appear to improve treatment outcomes, regardless of PZA susceptibility or duration of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[ 30 , 31 ] Our study reaffirms a previous study that showed Hangzhou as having a higher MDR-TB treatment success rate (73.7%) than other areas of China. [ 22 ] This study's success rate is higher than rates seen in most resource-limited countries [ 15 , 32 34 ] but lower than success rates of resource-rich counties. [ 11 , 35 , 36 ] When compared to cure rates from other countries, we should note that the successful treatment rate in our study included both cure and completion of treatment according to Chinese guidelines; the successful treatment rate (75.6%) was slightly higher than the cure rate (71.4%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[ 30 , 31 ] Our study reaffirms a previous study that showed Hangzhou as having a higher MDR-TB treatment success rate (73.7%) than other areas of China. [ 22 ] This study's success rate is higher than rates seen in most resource-limited countries [ 15 , 32 34 ] but lower than success rates of resource-rich counties. [ 11 , 35 , 36 ] When compared to cure rates from other countries, we should note that the successful treatment rate in our study included both cure and completion of treatment according to Chinese guidelines; the successful treatment rate (75.6%) was slightly higher than the cure rate (71.4%).…”
Section: Discussionmentioning
confidence: 94%
“…Treatment success rates range from 34.5% to 81% globally, [ 10 14 ] and factors associated with failure of treatment included higher prevalence of XDR-TB, HIV co-infection, use of standardized treatment regimens rather than individualized ones, and incomplete or non-adherent treatment. [ 10 , 12 , 15 18 ] There is limited Chinese research on the outcomes of MDR-TB treatment. [ 19 22 ] In this study, we aimed to evaluate the trend of treatment success across time and to identify factors associated with unsuccessful treatment outcomes in a cohort of MDR/XDR-TB patients in Hangzhou, China.…”
Section: Introductionmentioning
confidence: 99%
“…PZA was always controversial in the treatment of MDR-TB and XDR-TB, some studies showed that PZA resistant or not did not impact its anti-microbial activity (21,26,27), however, the high resistant rate of PZA had been considered its application in the future (28). In the present study, we tested PZA resistance by MIC value, the resistance rate was 50.9%.…”
Section: Discussionmentioning
confidence: 83%